How clientelism undermines state capacity: Evidence from Mexican municipalities - Ana L. De La O (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Does clientelism perpetuate the weak state capacity that characterizes many young democracies? Prior work explains that clientelist parties skew public spending to private goods and under-supply public goods. Building on these insights, this article argues that clientelism creates a bureaucratic trap. Governments that rely on clientelism invest in labour-intensive, low-skilled bureaucracies that can design and implement relatively more straightforward distributive policies. Although such bureaucracies are useful to win some elections, they cannot resolve more complex social problems, so economic and human development is hindered. Empirically, the article examines the wage structure of municipal bureaucracies as a proxy for the personnel's human capital in Mexico between 2012 and 2016. During this period, turnover in the party in power in municipalities was frequent, a situation that also allows investigating how resilient the bureaucratic trap is to increased competition. The results show that all parties invest in labour-intensive, lowskilled bureaucracies. However, the bureaucratic trap has a different grip on the Institutional Revolutionary Party (PRI), a quintessential clientelist party, compared to other parties. After an electoral turnover, other parties invest more in their bureaucracies' human capital, and the PRI does not. While prior work has proposed other clientelism-induced negative equilibria, this article offers a more direct path from clientelism to state capacity. The results help explain why more fiscal resources, political competition, and demand-side strategies to fight vote buying are insufficient and underscore the importance of civil service reform to tame clientelism.
Keywords: H10; H41; H75; 330; clientelism; state capacity; bureaucratic capacity; turnover; political competition